การศึกษานำร่องผลของการให้โปรแกรมส่งเสริมการทำงานสมองต่อการทำงานสมองและสมรรถภาพทางกายในผู้ป่วยปอดอุดกั้นเรื้อรังระดับความรุนแรงปานกลางถึงหนัก: การศึกษานำร่องผลของการให้โปรแกรมส่งเสริมการทำงานสมองต่อการทำงานสมองและสมรรถภาพทางกายในผู้ป่วยปอดอุดกั้นเรื้อรังระดับความรุนแรงปานกลางถึงหนัก - ปิยอมรพันธุ์, นิธิตา; วรวัฒนาชัย, ศุภกานต์; จีนประชา, ฐิติมา; ชั่งหนิ, มารินี; โต๊ะหลี, สุนิษา; โพธา, โฆษณพงศ์; สันติวรกุล, อโนมา; ดำช่วย, ทิพวิมล (ASEAN Journal of Rehabilitation Medicine, 2017)
Objectives: To investigate the effects of cognitive improvement program on cognitive function, physical function, and quality of life in patients with COPD performing routine endurance exercise. Study design: Experimental study. Setting: Maharaj Nakhon Si Thammarat hospital. Methods: Fourteen patients with moderate to severe COPD were randomly divided into 2 groups. The patients in control group performed traditional pulmonary rehabilitation program 40 minutes/day, 5 days/week for 4 weeks. The patients in experimental group also received the same pulmonary rehabilitation program. In addition, these patients were trained cognitive improvement program for 45 minutes/day, 2 days/week for 4 weeks. Cognitive function, physical function, and quality of life were evaluated before and after the interventions by using 6MWT, MoCA-B, and EQ-5D-5L, respectively. Results: Pulmonary rehabilitation could better 6MWT. However, it did not change cognitive function and quality of life. In the other hand, pulmonary rehabilitation plus cognitive improvement program significantly improved all observed parameters including cognitive function (p=0.003), walking distance (p=0.001), and quality of life (p=0.038). Additionally, it further increased physical function comparing to that in patients gaining a month-pulmonary rehabilitation (p=0.004). Conclusion: A combination of pulmonary rehabilitation and cognitive therapy are likely to be more effective than pulmonary rehabilitation alone.